Vaccinia virus A11 is required for membrane rupture and viral membrane assembly - Suárez García, Cristina; Hoppe, Simone; Krijnse-Locker, Jacomine (Cellular microbiology, 2017)
Although most enveloped viruses acquire their membrane from the host by budding or by a wrapping process, collective data argue that nucleocytoplasmic large DNA viruses (NCLDVs) may be an exception. The prototype member of NCLDVs, vaccinia virus (VACV) may induce rupture of endoplasmic-reticulum-derived membranes to build an open-membrane sphere that closes after DNA uptake. This unconventional membrane assembly pathway is also used by at least 3 other members of the NCLDVs. In this study, we identify the VACV gene product of A11, as required for membrane rupture, hence for VACV membrane assembly and virion formation. By electron tomography, in the absence of A11, the site of assembly formed by the viral scaffold protein D13 is surrounded by endoplasmic reticulum cisternae that are closed. We use scanning transmission electron microscopy-electron tomography to analyse large volumes of cells and demonstrate that in the absence of A11, no open membranes are detected. Given the pivotal role of D13 in initiating VACV membrane assembly, we also analyse viral membranes in the absence of D13 synthesis and show that this protein is not required for rupture. Finally, consistent with a role in rupture, we show that during wild-type infection, A11 localises predominantly to the small ruptured membranes, the precursors of VACV membrane assembly. These data provide strong evidence in favour of the unusual membrane biogenesis of VACV and are an important step towards understanding its molecular mechanism.
Gesehen am 21.07.2020